PENGARUH KEPUASAN PELANGGAN TERHADAP KINERJA KEUANGAN MELALUI LOYALITAS PELANGGAN SEBAGAI VARIABEL INTERVENING PADA BERBAGAI SEKTOR PERUSAHAAN DI INDONESIA - Lisa Maritseda Prakarsa (Business Accounting Review, 2016)
This study aimed to examine the affect between customer satisfaction and financial performance through customer loyalty as the intervening variable. Samples used in this study were 60 samples (firm-years) from various sectors listed in Indonesia Stock Exchange during the period 2011-2014. The hypothesis were tested by using Partial Least Square (PLS). Customer satisfaction showed the influence to the customer loyalty and company's financial performance. The size of company’s performance in this study are return on assets (ROA), return on equity (ROE), and net profit margin (NPM).